Edukasi Financial Melalui Analisis Estimasi Biaya dalam Keseharian Bagi Siswa SMK Assa'adah: Financial Education Through Cost Estimation Analysis in Daily Life For Students at Assa'adah Vocational High School - Purwanto; Akhmad Wasiur Rizqi; Nina Aini Mahbubah (JURNAL PENGABDIAN MANAJEMEN, 2026)
Financial education is an essential competency in developing rational and sustainable economic behavior, particularly among secondary school students. Various studies indicate that students' financial literacy levels are still relatively low. This study aims to analyze the effectiveness of financial education through a cost estimation analysis approach in improving financial literacy and daily financial management behavior in vocational high school students. The study used a quantitative approach with a pre-test and post-test design supported by qualitative data. The study subjects consisted of 15 vocational high school students who participated in a cost estimation-based financial education program. The research instruments included a financial literacy test, daily cost estimation and realization sheets, as well as interviews and observations. The results showed a significant increase in students' financial literacy scores, with an average pre-test score of 55.47 increasing to 77.87 in the post-test. In addition, 60% of students were able to prepare expenditure estimates that were appropriate or more economical than actual costs. Qualitative findings indicated increased financial awareness, the ability to distinguish between needs and wants, and control consumptive behavior. This study concluded that financial education based on cost estimation analysis is effective in improving financial literacy while fostering more responsible financial management behavior. This approach is applicable, contextual, and has the potential to be developed as a financial literacy learning model in school environments.